Changes in private psychiatric practice in Australia: An analysis of trends in claims for outpatient Medicare item numbers over 14 years. (August 2022) - Forbes, Malcolm; Sizer, Holly; Khanna, Rahul; Hopwood, Malcolm; Green, Jessica; Pring, Bill
Objective: The Better Health Access Initiative added 32 Medicare Benefits Schedule (MBS) item numbers in 2006 to increase the number of people with access to mental health care. We investigated trends in the provision of outpatient Medicare-subsidised psychiatric services since the introduction of these item numbers in 2006 through 2019. Methods: Medicare Benefits Schedule aggregated item-number claims data were obtained from the Services Australia Medicare website, between January 2006 and December 2019 inclusive, for face-to-face psychiatrist consultations. Item number rates were collated and graphed per 100, 000 population according to year and item number. Results: There has been an increase in the number of claims for new patient assessments (291–296) and a reduction in most ongoing care Medicare item numbers, especially longer appointments that are often associated with psychotherapy provision (306–308). Conclusion: There have been changes in private psychiatric practice in Australia over the past 14 years. There are several possible causes for these changes and further research is required to determine the impact on patient care.